Rereading Frye : The Published and the Unpublished Works - Boyd, David (David V.); Salusinszky, Imre, 1955- (Book collections on Project MUSE., 1999)
"Following Northrop Frye's death in 1991, a large archive of his correspondence, unpublished criticism, and notebooks was deposited with the Victoria University Library at the University of Toronto. This collection of essays, written by a distinguished group of Frye experts, begins the process of reassessing Frye's thought and writings in light of the extraordinary material contained in this archive."--Jacket.